2013
DOI: 10.3109/19390211.2013.822450
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective, Antioxidant, and Ameliorative Effects of Ginger (Zingiber officinale Roscoe) and Vitamin E in Acetaminophen Treated Rats

Abstract: Ginger is a remedy known to possess a number of pharmacological properties. This study investigated efficacy of ginger pretreatment in alleviating acetaminophen-induced acute hepatotoxicity in rats. Rats were divided into six groups; negative control, acetaminophen (APAP) (600 mg/kg single intraperitoneal injection); vitamin E (75 mg/kg), ginger (100 mg/kg), vitamin E + APAP, and ginger + APAP. Administration of APAP elicited significant liver injury that was manifested by remarkable increase in plasma alanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 64 publications
7
24
1
Order By: Relevance
“…Liver of rats from all GAE-treated groups (protected, treated and combination) showed normal hepatic parenchyma with very mild round cells infiltrations in the portal areas indicating that ginger could restore the hepatotoxic effect caused by IMI. These results agree with previous studies Abdel- Azeem et al (2013). Also coadministration of ginger with piroxicam revealed somewhat normal histological architecture of liver (Badawi, 2018).…”
Section: Ne Ussupporting
confidence: 93%
“…Liver of rats from all GAE-treated groups (protected, treated and combination) showed normal hepatic parenchyma with very mild round cells infiltrations in the portal areas indicating that ginger could restore the hepatotoxic effect caused by IMI. These results agree with previous studies Abdel- Azeem et al (2013). Also coadministration of ginger with piroxicam revealed somewhat normal histological architecture of liver (Badawi, 2018).…”
Section: Ne Ussupporting
confidence: 93%
“…Also, previous investigators demonstrated that ginger oil had a dominative protective effect on DNA damage and might act as a scavenger of oxygen radicals [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Zingiber officinale (or ginger), is one of the most extensively used herbs in the Indian system of traditional medicine. Many studies have revealed its numerous pharmacological activities, such as, antioxidant, antibacterial, anti-inflammatory, antinociceptive [ 15 ], antimutagenic [ 16 ] and hepatoprotective [ 17 ]. Furthermore, there are several other studies showing the antibacterial effect of Z. officinale against a number of micro-organisms including S. mutans [ 18 - 20 ].…”
Section: Introductionmentioning
confidence: 99%